2018
DOI: 10.1007/978-3-030-04807-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Instability of the Akhmediev Breather and a Finite-Gap Model of It

Abstract: The focusing Nonlinear Schrödinger (NLS) equation is the simplest universal model describing the modulation instability (MI) of quasi monochromatic waves in weakly nonlinear media, considered the main physical mechanism for the appearance of rogue (anomalous) waves (RWs) in Nature. In this paper we study the numerical instabilities of the Akhmediev breather, the simplest space periodic, one-mode perturbation of the unstable background, limiting our considerations to the simplest case of one unstable mode. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In the second subcase in which more than one unstable gap is open, we obtain the elementary description of the first nonlinear stage of MI, given again by the Akhmediev 1-breather solution, and how perturbations due to numerics and/or real experiments can affect this result. In addition, in [26] we have shown that the finite gap recurrence formulas constructed in [25] are a good model for describing the numerical (and physical) instabilities of the Akhmediev breather.…”
mentioning
confidence: 92%
“…In the second subcase in which more than one unstable gap is open, we obtain the elementary description of the first nonlinear stage of MI, given again by the Akhmediev 1-breather solution, and how perturbations due to numerics and/or real experiments can affect this result. In addition, in [26] we have shown that the finite gap recurrence formulas constructed in [25] are a good model for describing the numerical (and physical) instabilities of the Akhmediev breather.…”
mentioning
confidence: 92%
“…To conclude, the disagreement between the analytic breather solution of the NLS equation and its numerical simulation presented here (Fig. 2) can occur due to the following reasons (see also [28]): i) due to the different dynamical features of the continuous partial differential equation and its discrete counterpart;…”
Section: Simulations Of the Nonlinear Schrodinger Equationmentioning
confidence: 82%
“…The perturbations may be a numerical noise which cannot be removed completely, thus the situation when the excitation of one unstable mode leads to the development of all available unstable modes represents the general picture (see, e.g., in [12,27]). The impact of different numerical effects on the accuracy of the simulation of the Akhmediev breathers was also in the focus of the study [28].…”
Section: The Circumstances Which Can Prevent the Full Recurrence Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that they are unstable with respect to small perturbations of the NLS equation [42,67,24,25]; see also a finite-gap model describing the numerical instabilities of the AB [37].…”
Section: Introductionmentioning
confidence: 99%